LAJU FUNGSI LINDUNG DAS SECARA TEMPORAL BERDASARKAN DATA PENGINDERAAN JAUH DI KABUPATEN SINJAI - Muhlis Muhlis; Garwan Khalid; Fatmawati Fatmawati; Rakhmad Armus; Sappewali Sappewali; C. Selry Tanri (KOLONI, 2022)
Land cover change is a transition process, such as agricultural land does not immediately turn into built-up land but into grass/soil or shrubs land cover change the transition process of land cover change. This study aims to (1) Determine the rate of change in the temporal function of the hedge. (2) Determine the value of the protection coefficient based on the results of satellite imagery analysis. The method used in this study is spatial descriptive, with land units as units of analysis or mapping units. In spatial description, the results of the study will be described and displayed in the form of a map. In this study, it will be described spatially and temporally the land cover and its effect on the index of protected function of the research area (Sinjai Regency Watershed). The analysis used is spatial analysis whose processing uses a Geographic Information System, with outputs including Land Use Maps and Land Cover Maps. In the period 2014 - 2022, there was a dynamic change in land cover in the Sinjai Regency watershed. The largest land cover that has changed is miscellaneous use which changed 49.87%, then mixed land which changed 24.66% and water body 12.20%. The index of the protected function of the Sinjai Regency Watershed in 2014 was 0.57 and in 2022 it was 0.50. During the period 2014-2022 there was an increase in the hedging function index by 0.02. Keywords: Temporal, Protected coefficient, Spatial